PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, KUALITAS AUDIT, OPINI AUDIT, KOMITE AUDIT TERHADAP AUDIT REPORT LAG - Ni Made Sunarsih; Ida Ayu Budhananda Munidewi; Ni Kadek Mirah Masdiari (KRISNA: Kumpulan Riset Akuntansi, 2021)
Audit report lag is the time span required to complete the audit conducted by the auditor as measured by the time difference between the date of the financial statements and the date of the audit opinion in the financial statements. The length of time it takes for the auditor to audit the company's financial statements can have an impact on decision making by various parties. Therefore, financial reports must be presented accurately and in a timely manner so that they are more useful for those who need information. The purpose of this study was to determine the effect of company size, solvency, profitability, audit quality, audit opinion and audit committee on audit report lag. This research was conducted at mining companies listed on the Indonesia Stock Exchange 2016-2018. The type of data used is quantitative data in the form of audited financial reports along with notes on financial reports and qualitative data in the form of mining company data. The sample used was 41 companies with a total of 123 observations, with a purposive sampling method. The analysis technique used is multiple linear regression analysis. The result showed that company size has a positive effect on audit report lag. Solvency and audit quality have a negative effect on the audit report lag. Profitability, audit opinion, and audit committee have no effect on the audit report lag. Further research can develop this research by using other variables which theoretically have an effect on the audit report lag, such as changes in auditors and the board of commissioners.